Analisis Kualitatif Pemanfaatan Aplikasi Google dalam Kerja Kelompok Kolaboratif Daring - Fikri Nur Hammam; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
2019 was the beginning of the COVID-19 pandemic in Wuhan, China. The pandemic caused the government to implement PSBB (Large-Scale Social Restrictions). One of the areas directly affected is the education sector. The PSBB has caused the teaching and learning process that should have taken place face-to-face now can only be done online. Students use technology to support their teaching and learning process. One of the technologies used by students is cloud computing. Cloud computing features help students work collaboratively on assignments online. In this study, qualitative research was conducted to determine student behavior and also the obstacles experienced by them. This research was conducted by means of semi-structured interviews. After the interviews were conducted, the researcher conducted a transcript. The results of the interview transcripts were then continued with the analysis process. In this study, the thematic analysis method was used. The results of the analysis then produce behavioral findings and also the obstacles experienced by students when using cloud computing for online collaborative group work. The results of this study are the findings of student behavior during online collaborative group work such as student behavior before cloud computing was widely used, student behavior when choosing their own group, student behavior when selected by a group by lecturers, supportive group mates behavior, inhibiting groupmate behavior, student behavior when discussing online, student behavior when discussing offline, behavior towards friends is less cooperative. And also found obstacles experienced by students such as obstacles to the use of cloud computing, group work constraints, lack of Google applications, security issues.